Early Machine Learning Research in Ljubljana - Kononenko, Igor (Informatica, 2018)
<span style="color: black; line-height: 107%; font-family: 'Times New Roman',serif; font-size: 11pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">We describe early machine learning research in Ljubljana, motivated by medical diagnostic problems, in the areas of building decision trees with Assistant, the development of Naïve and Semi-Naïve Bayesian classifier and its explanations of individual predictions, and the development of ReliefF and RReliefF algorithms for non-myopic evaluation of attributes in classification and regression, respectively.